Volume 5: Controls, Diagnostics, and Instrumentation; Cycle Innovations; Cycle Innovations: Energy Storage 2020
DOI: 10.1115/gt2020-14932
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Profiling of Cooled Radial Turbine Wheel

Abstract: Compliance with incoming new emission standards such as Euro6d and China6b will require new approaches to the design of thermally loaded automotive components e.g. turbochargers, exhaust valves and manifolds. However, the validation of those new designs and the need for a rapid market entry will require new temperature measurement technologies to provide accurate data across the entire component. A limited number of techniques are currently available, and all have limitations in the harsh operating conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Given that the gas power turbine is one of the major sources of generating power (electric power), research has shown that the inefficiency of most of these GTs is a result of the ignorance displayed in the aspect of Fuel supply into the system, either in quality or conditional state of the fuel gas. Hence there is much need to research, study and improve upon existing research on fuel (gas) and its effect on gas turbines' performances and output [11]. This research is important to the development of the power sector -generation, distribution and transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the gas power turbine is one of the major sources of generating power (electric power), research has shown that the inefficiency of most of these GTs is a result of the ignorance displayed in the aspect of Fuel supply into the system, either in quality or conditional state of the fuel gas. Hence there is much need to research, study and improve upon existing research on fuel (gas) and its effect on gas turbines' performances and output [11]. This research is important to the development of the power sector -generation, distribution and transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing is also finding application for various components in reciprocating engines, to again improve efficiency and reduce emissions. Some of the most noteworthy research includes additively manufactured radial turbines for automotive turbochargers with AM-enabled internal cooling features, 22 the work conducted on improving pistons via topology optimization, 23 and combustion bowls for diesel engines. 24…”
Section: Introductionmentioning
confidence: 99%